(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The integration of computer programs in music education has revolutionized the way students engage with music theory, composition, and performance. This article explores the methodology of incorporating digital tools such as digital audio workstations (DAWs), music notation software, ear training apps, and interactive music theory platforms into music lessons. By examining data from music educators, classroom observations, and student surveys, the study highlights the benefits and challenges associated with technology-enhanced music education. Findings indicate that computer programs enhance student engagement, foster creativity, and improve aural skills, while also providing greater accessibility for diverse learning needs. However, issues such as technical support, teacher preparedness, and balancing traditional teaching methods with digital tools present challenges that need to be addressed. The article concludes that, when integrated effectively, computer programs can significantly enhance the learning experience and help students develop a more comprehensive understanding of music.